Assessing and validating young Kazakhstanis’ reading skills in English, the impact of classroom climate, and their engagement on reading skills - Aigul Akhmetova; Soeharto Soeharto; Gaysha Imambayeva; Benő Csapó (Universitas Pendidikan Indonesia, 2022)
Improving reading skills in English for young Kazakhstani learners is a challenging process, but it was unfortunate that teachers in Kazakhstan do not frequently apply and implement assessments in the context of a school or classroom. Following a pilot study conducted in 2018, a continuous assessment was considered necessary to highlight the errors and challenges related to such unfortunate condition. This study performed validation and assessment of reading skills in English as a foreign language (EFL) within a classroom climate and in relation to the engagement of students in grades 6 and 8 in Kazakhstan. The participants were chosen randomly from seven secondary schools in a major city. The first language of all the participants (N = 1,206) was either Kazakh or Russian. Data from 906 students following data screening were analyzed. EFL Reading comprehension tests and a questionnaire regarding the students’ classroom climate and engagement were administered via the eDia online assessment platform. The analysis involved an exploratory factor analysis, a confirmatory factor analysis, and an internal consistency test using Cronbach’s alpha, composite reliability, and construct validity. To determine the effects of factors detected from the background variables on students’ reading results in EFL, a regression analysis was conducted. As results, no gender differences were found for either grade. However, in grade 6, students whose first language was Kazakh performed better than the students whose first language and/or language spoken at home was Russian. In grade 8, the differences between Kazakh and Russian students were negative but non-significant. Nevertheless, despite the weak relationship between the latent factors and reading skills, both grades showed a good model fit to the data and good factor loadings. Implication of the study and further research are also discussed.